Dragon's Halloween - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Dragon, 2020)
Dragon is looking forward to Halloween: carving pumpkins, attending a costume party, and making pumpkin treats--but as usual things do not go smoothly.